A cooperative system of silicon transport in plants - Ma, Jian Feng; Yamaji, Naoki (Trends in plant science, 2015)
•There are two types of silicon transporter with different polarity and cellular localization.•Cooperation of influx and efflux Si transporters is required for efficient Si uptake and distribution. The high accumulation of silicon (Si) protects plants from biotic and abiotic stresses. Two different types of Si transporter [Low Silicon 1 (Lsi1) and 2 (Lsi2)] involved in the uptake and distribution of Si have been identified. Lsi1, a Si permeable channel, belongs to the Nod26-like major intrinsic protein (NIP) III subgroup of the aquaporin membrane protein family with a distinct selectivity, whereas Lsi2, an efflux Si transporter, belongs to an uncharacterized anion transporter family. These transporters are localized to the plasma membrane, but, in different plant species, show different expression patterns and tissue or cellular localizations that are associated with different levels of Si accumulation. A recent mathematical modeling study revealed that cooperation of Lsi1 and Lsi2, which show a polarized localization, is required for the efficient transport of Si in rice. [Display omitted]